Topical issues of introduction of criminal offenses in the legislation of Ukraine - Книженко, Оксана Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The problems of the introduction of criminal offenses in Ukraine have been elaborated. Attention has been brought to the fact that the signing of number of regulations recognizing human rights and freedoms as priorities makes our State take a different look at the problem of the Criminal Code of Ukraine. Unlike the criminal legislation of 1960, the primary tasks of which were, among others, defence of the social system of Ukraine, its political and economic systems, the 2001 Criminal Code of Ukraine brings the legal protection of the rights and freedoms of man and citizen to the forefront. This formulation of the tasks of criminal law has become a turning point for Ukraine, which is marked by a significant humanization process since 2001. These processes serve as a basis for an idea of introducing the notion of offences in the Criminal Code of Ukraine. The paper points out the problems that hinder the statutory consolidation of the institution of offences in our country. It is highlighted that one of the factors that prevents this process is the traditional domestic view of the criminal law as purely punitive, which can only define crimes and punishment. Another important factor is shallow analysis of international experience on this subject, the study of which is essential during the introduction of the institution of criminal offenses. So, one of the ways to solve the problem of introducing criminal offences to the national legislation is a need to study the international experience on these issues. In particular, this paper analyzes the French legislation regarding the classification of criminal offences. It is noted that criminal offences under the Criminal Code of France are divided into crimes, misdemeanors and violations. This classification is based on the graveness of these offences. Depending on the type of criminal offence, a person undergoes appropriate measures of legal and procedural impact. It is concluded that the introduction of the institution of criminal offences in the legislation should be preceded by an in-depth analysis of international practices, which will serve as a «platform» for the development of the national legislation on criminal offences.